Do CEO Characteristics affect Financial Reporting Quality? An Empirical Analysis: Array - Ashafoke, Tina; Dabor, Eyesan; Ilaboya, James (Acta Universitatis Danubius. Œconomica, 2021)
This research explores the effect of CEO characteristics on financial reporting quality of listed financial firms. This research, with a sample of 15 firms operating in Nigeria's financial institutions from 2008 - 2019, drew insights from the upper echelon theory to investigate the effect of CEO characteristics on the financial reporting quality. CEO characteristics was measured using variables such as CEO gender, CEO financial expertise and CEO tenure. We analysed the data using the panel regression analysis. Empirically, the results showed that there is a positive and insignificant relationship between the CEO gender and financial reporting quality. CEO financial expertise revealed a negative and significant relationship with financial reporting quality. While, CEO tenure revealed a positive and significant relationship with financial reporting quality. The study recommend that internal and external regulatory board should ensure that a maximum CEO tenure is fixed for all listed firms.